2010
DOI: 10.1002/gps.2607
|View full text |Cite
|
Sign up to set email alerts
|

Determining the minimum clinically important differences for outcomes in the DOMINO trial

Abstract: Reference to MCIDs is important for the full interpretation of the results of dementia trials and those conducting such trials should be open about the way in which they have determined and chosen their values for the MCIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 28 publications
(28 reference statements)
6
127
3
1
Order By: Relevance
“…Whereas the psychometric changes in the placebo arm are in keeping with observed changes reported elsewhere in similar populations, 28,29 the change in ADAS-cog was double than anticipated. 4 While every attempt was made to improve internal validity by ensuring raters received the same psychometric rating training and, wherever possible, not change between visits, small numbers in the study cannot rule out the random allocation of a more rapidly declining group to the placebo arm and differences between groups should be viewed with caution.…”
Section: (1) 4 (3)supporting
confidence: 71%
“…Whereas the psychometric changes in the placebo arm are in keeping with observed changes reported elsewhere in similar populations, 28,29 the change in ADAS-cog was double than anticipated. 4 While every attempt was made to improve internal validity by ensuring raters received the same psychometric rating training and, wherever possible, not change between visits, small numbers in the study cannot rule out the random allocation of a more rapidly declining group to the placebo arm and differences between groups should be viewed with caution.…”
Section: (1) 4 (3)supporting
confidence: 71%
“…At least for the area of quality of life, there is empirical evidence of the suitability of such an MID [35]. In the recent DOMINO trial in moderate to severe AD, however, MIDs were suggested for cognition (MMSE) and function (Bristol ADLs Scale) based on 0.4 of the SD, since this produced values which aligned the closest with the opinion of the investigators [36,37]. In the literature, various methods have been used to estimate MIDs for patient-reported outcome instruments (for a review, see [34]) - from consideration of the statistical distribution of scores, to anchor-based methods in which the MID is determined by comparing the scale to real-life criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no significant intergroup difference on the MMSE, the cost-effectiveness analyses suggest that MCST would be a cost-effective addition to usual care at low willingness-to-pay thresholds. Howard et al 19 suggested that a difference of 1.4 on MMSE is clinically significant; the mean cost of achieving this difference through MCST is £781.…”
Section: Cost-effectiveness (At 6 Months)mentioning
confidence: 99%